Improving Critical Thinking Skills By Using Problem Learning Models Based Learning In Grade V Students - ANASTA, ST. VANEZHA; Supriadi, Supriadi; Nurdiansyah, Erwin (ALENA : Journal of Elementary Education, 2025)
This study aims to find out: (1) The application of the problem-based learning model in grade V students of SDN 019 Sabbang, North Luwu Regency. (2) critical thinking skills in grade V students of SDN 019 Sabbang, North Luwu Regency. (3) The problem-based learning model can improve critical thinking skills in grade V students of SDN 019 Sabbang, North Luwu Regency by using the type of classroom action research (PTK) which consists of 2 cycles, namely cycles I and II, where each cycle consists of three meetings with four stages, namely planning, implementation, observation, and reflection. (4) PTK results in cycle I are categorized as lacking, where most students still have low learning outcomes and thinking skills. Furthermore, in cycle II, it is categorized as good, where the average student has high learning outcomes and critical thinking skills. (5) Critical thinking skills can be improved by applying the problem-based learning model in grade V students of SDN 019 Sabbang, North Luwu Regency.